2021
DOI: 10.1093/ofid/ofab159
|View full text |Cite
|
Sign up to set email alerts
|

The Global Epidemiology of RSV in Community and Hospitalized Care: Findings From 15 Countries

Abstract: Background Respiratory syncytial virus (RSV) is one of the leading causes of acute respiratory tract infections. To optimize control strategies, a better understanding of the global epidemiology of RSV is critical. To this end, we initiated the Global Epidemiology of RSV in Hospitalized and Community care study (GERi). Methods Focal points from 44 countries were approached to join GERi and share detailed RSV surveillance data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 27 publications
0
60
0
1
Order By: Relevance
“…One method could therefore be applied to analyze RSV seasonality allowing for comparison between countries. A limitation of an analysis that compares seasonality across countries might be the discrepancies in surveillance systems as previously described, 22 with factors such as case definitions and the surveillance setting potentially having implications on the estimation of RSV seasonality. 32 Another limitation of our study is the lack of representation of several regions of the world as no data from countries in North Africa or the Middle East were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method could therefore be applied to analyze RSV seasonality allowing for comparison between countries. A limitation of an analysis that compares seasonality across countries might be the discrepancies in surveillance systems as previously described, 22 with factors such as case definitions and the surveillance setting potentially having implications on the estimation of RSV seasonality. 32 Another limitation of our study is the lack of representation of several regions of the world as no data from countries in North Africa or the Middle East were included.…”
Section: Discussionmentioning
confidence: 99%
“…The GERi network, consisting of 16 countries, and the surveillance systems from which the virological data have emerged have been described previously. 22 Briefly, data were stratified by level of care (hospitalized and community) and both case definitions (ILI at community level and SARI at hospitalized level), and diagnostic methods were largely similar across participating countries. For the current analysis, seasons containing <100 cases at national level were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Testing for RSV in adults by internists and general practitioners is rare, partially due to lack of awareness (14). A recent international study conducted across 15 countries reported that cases of RSV in adults ≥ 65 years old were notably under-represented in national surveillance programs (15). RSV testing is also limited in the younger population as shown by a prospective study in pediatric patients (≤18 years old) in Germany, which revealed that only 8.7% of patients presenting with symptoms of a respiratory tract infection underwent viral diagnostic testing during standard-of-care procedures (16).…”
Section: Introductionmentioning
confidence: 99%
“…First, RSV infections are not assessed in routine clinical practice and are underdiagnosed. Second, clinical symptoms of RSV-associated acute respiratory illnesses (ARIs) overlap with those of other prevalent viral respiratory diseases (10,11). Third, there is a lack of consensus on the ARI case definition (10).…”
Section: Introductionmentioning
confidence: 99%
“…Third, there is a lack of consensus on the ARI case definition (10). In older adults, the estimation of RSV-associated ARI incidence rates is further complicated by the low viral loads of RSV infections and the relatively poor sensitivity of diagnosis methods (10,11), even if these have improved markedly in the last decades with the development of molecular techniques, e.g., polymerase chain reaction (PCR) (12).…”
Section: Introductionmentioning
confidence: 99%